Dehydroepiandrosterone (DHEA) increases undirected singing behavior and alters dopaminergic regulation of undirected song in non-breeding male European starlings (Sturnus vulgaris) - Heimovics, Sarah; Rubin, Nathan; Ford, Morgan (Frontiers in Endocrinology, 2023)
It has been proposed that in species that defend territories across multiple life history stages, brain metabolism of adrenal dehydroepiandrosterone (DHEA) regulates aggressive behavior at times when gonadal androgen synthesis is low (i.e. the non-breeding season). To date, a role for DHEA in the regulation of other forms of social behavior that are expressed outside of the context of breeding remains unknown. In this experiment, we used the European starling (Sturnus vulgaris) model system to investigate a role for DHEA in the neuroendocrine regulation of singing behavior by males in non-breeding condition. Starling song in a non-breeding context is spontaneous, not directed towards conspecifics, and functions to maintain cohesion of overwintering flocks. Using within-subjects design, we found that DHEA implants significantly increase undirected singing behavior by non-breeding condition male starlings. Given that DHEA is known to modulate multiple neurotransmitter systems including dopamine (DA) and DA regulates undirected song, we subsequently used immunohistochemistry for phosphorylated tyrosine hydroxylase (pTH, the active form of the rate-limiting enzyme in DA synthesis) to investigate the effect of DHEA on dopaminergic regulation of singing behavior in a non-breeding context. Pearson correlation analysis revealed a positive linear association between undirected singing behavior and pTH immunoreactivity in the ventral tegmental area and midbrain central gray of DHEA-implanted, but not control-implanted, males. Taken together, these data suggest that undirected singing behavior by non-breeding starlings is modulated by effects of DHEA on dopaminergic neurotransmission. More broadly, these data expand the social behavior functions of DHEA beyond territorial aggression to include undirected, affiliative social communication.